2011
DOI: 10.1353/bio.2011.0005
|View full text |Cite
|
Sign up to set email alerts
|

Recent Trends in Using Life Stories for Social and Political Activism

Abstract: Lifestory-sharing sites have never been as popular as today. These sites interpret the act of “sharing” life stories as a form of communal endeavor, and argue that publicly shared life stories will lead to more inclusive communities and to more effective forms of participatory democracy. The present article studies the rhetoric of this new form of lifestory-based activism, and suggests that we need to be cautious about accepting some of its more idealistic claims.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…In another example, DST can be used as an advocacy tool to contribute to policy processes. For policy makers, stories outline individuals' and communities' needs and priorities; for communities, engagement in consultations and decision-making can be more meaningful through recorded storytelling (Lénárt-Cheng and Walker, 2011). DST thus offered a creative means of engaging with the women in this study on an individual basis, and became an effective means of 'collecting' or gathering narratives that usually remain in the private sphere, and sharing them with significant others.…”
Section: Discussionmentioning
confidence: 99%
“…In another example, DST can be used as an advocacy tool to contribute to policy processes. For policy makers, stories outline individuals' and communities' needs and priorities; for communities, engagement in consultations and decision-making can be more meaningful through recorded storytelling (Lénárt-Cheng and Walker, 2011). DST thus offered a creative means of engaging with the women in this study on an individual basis, and became an effective means of 'collecting' or gathering narratives that usually remain in the private sphere, and sharing them with significant others.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work on storytelling and e-advocacy argued that organizers continue to play a fundamental role in ensuring that the narratives that result from these emerging participatory techniques are both coherent and effective (Vromen and Coleman, 2013). Similarly, others pointed out that there is likely a tradeoff between maintaining the spontaneity of crowd-sourced personal stories and their efficacy in influencing policy-making processes (Lenart-Cheng and Walker, 2011: 150–151). Yet, the #SpartacusStories case study analyzed here showed that it is possible to generate a coherent counter-narrative by taking a relatively hands off approach to story-based online campaigns.…”
Section: Discussionmentioning
confidence: 99%
“…The first British advocacy group to launch a campaign featuring personal life stories was a digital network of disabled bloggers turned activists called The Broken of Britain. Having kept personal blogs for several years already, these young disabled individuals joined forces in 2010 and capitalized on the growing popularity of lifestyle blogs (Lenart-Cheng and Walker, 2011) to launch a new type of disability advocacy that used a range of innovative techniques (Trevisan, 2016). Among these, The Broken of Britain’s organizers invited other disabled Internet users to share their personal stories publicly on Twitter using the #MyDLA (short for ‘My Disability Living Allowance’) hashtag at critical moments during the welfare reform legislative process in 2011.…”
Section: Austerity As a Catalyst For Storytellingmentioning
confidence: 99%
“…‘In my effort to record my own life and a moment of gay history,’ he writes, ‘I seemed to have grasped something essential about growing up gay in America’ (Kantrowitz, 1996, 199). In 1976 he wrote in order to motivate gay readers to come out and join the gay movement, and to do that he personalizes history (Lénárt-Cheng and Walker, 2011).…”
Section: The Sexual Politics Of Militant Memoirsmentioning
confidence: 99%
“…They also offer social movement scholars unique insights into the subjectivity of social actors, especially participants in past social movements. Thus, not only sociologists, but also historians and even rhetoricians have analysed how memoirs, autobiographies, and life-stories have been produced as part of an effort to generate further mobilization in a given social movement (Lénárt-Cheng and Walker, 2011; Perkins, 2000; Taylor, 2009; Watson, 1999). This coincides with a more general trend in social movement sociology that approaches narratives as strategic tools for social movements (Benford, 2002; Polletta, 2006).…”
Section: Introductionmentioning
confidence: 99%